Epistimologi Islam dalam Perpsektif M. Abid Al Jabiri - Zaedun Na'im (Transformatif, 2021)
The development of the science of development is slowly growing rapidly, more so in the western world based on the main base, namely rationalism, and empiricism. However, it is in contrast to the treasures of Islamic scholarship which stagnated due to differences in perceptions of accepting or rejecting science which only stems from rationalism and empiricism. Based on this anxiety, there was an effort made by one of the leading Muslim figures named M. Abid Al Jabiri who tried to construct ideas about the importance of the development of science in Islamic treasures with an Islamic epistemological approach. Therefore, this paper was appointed to reveal more deeply how the views of M. Abid Al Jabiri in the development of Islamic scientific treasures with an Islamic Epistemology approach so that with his view it provides a solution to confusion and adversity in the development of Islamic scholarship. This study method uses a qualitative approach with the type of library research. Through this type of research, the author collects various references regarding the views of M. Abid Al Jabiri on Islamic epistemology which the authors then analyze and can finally produce a conclusion. The results of this study conclude that in M. Abid Al Jabiri's view, Islamic epistemology through Bayani, Irfan, and Burhani epistemologies is an answer to how important it is to use Islamic epistemology for the development of Islamic scholarship so that it does not lag behind the dominance of Western scientific development.